Pastoral care and dementia: Reflections on the role of empirical practical theology in counterbalancing constructions of dementia as crisis - Krause, Katharina (Crisis, fear and hope, 2023)
This chapter deals with conceptions of dementia-as crisis or critical event and corresponding professional discourse and practices in contexts of pastoral and spiritual care. It contrasts these conceptions with insights from an ethnographic research project with people living with dementia that explores worship practices in care-homes. Analyzing ‘dementia-as-crisis’ and dementia-related discourse and practice in contexts of pastoral care as simultaneous or co-constructing events, it reflects upon dichotomously organized role schemata and enactments which form the foundations of the dementia as-crisis dispositive. To illustrate its workings the researcher’s own entanglement into its ‘doings’ and ‘sayings’ is critically engaged with. On this basis, options for alternative conceptions and narratives of people living with dementia in pastoral discourse and practice are considered.